Prevalence and risk factors associated with traumatic dental injuries among 12-15 year old school going children, Mathura city - Roopali Gupta; Navpreet Kaur; Vivek Sharma; Manish Bhalla; Manvi Srivastava; Siddharth Sisodia (Wolters Kluwer Medknow Publications, 2021)
Background: Traumatic dental injuries are a serious public dental health problem throughout the world. The incidence of traumatic injuries is increasing over the years. Trauma to the permanent anterior teeth is a common finding. Dental trauma is an irreversible pathology that after the occurrence is characterized by a life-long debilitating effect. Aims and Objectives: The aim of this study was to estimate the prevalence and assess factors related to traumatic injuries to permanent anterior teeth among 12-15-year-old children attending private and government schools in Mathura city. Materials and Methods: An epidemiological cross-sectional study was carried out among 1000 school children aged 12-15 years in which 500 children from both government and private schools, respectively, of five geographical zones of Mathura city were randomly selected. Children completed a questionnaire related to the history of trauma to their anterior teeth after which they were examined for type of lip coverage, Angle's molar relationship, and incisor nature of trauma sustained. Statistical analysis: SPSS 21 was carried out using Student's t-test (P < 0.05), Chi-square test, and Mantel-Haenszel test. Results: The prevalence of traumatic injuries was 8.9% and was higher among government school children compared to private school children. The boys and girls with a history of trauma were 67.4% and 32.6%, respectively. The main cause of trauma was fall in the playground (46.0%). The main reason of trauma was because of pushing (65.2%). The most predominant injuries were enamel fractures and the most common place for occurrence was school. Conclusion: The prevalence of dental injuries in Mathura city was high and it has a great potential to be considered as an emerging public health problem.